Change in Calcaneal Bone Strength in Long-Term Care Residents Treated With Low-Intensity Pulsed Ultrasound. Issue 7 (July 2017) - Okuizumi, Hiroyasu; Koyano, Kiyoshi; Kurosawa, Kazuya; Kamide, Naoto; Soyano, Ayako
Abstract : Objective: We examined the effect of low-intensity pulsed ultrasound (LIPUS) on bone strength in osteoporotic elderly residents. Materials and Methods: This was a randomized controlled trial. Elderly residents with osteoporosis in a long–term care facility were treated with LIPUS (oscillation frequency 100 KHz) that involved treatment of the heel bone for 2 minutes a day. The selection of the treated heel was decided randomly with a personal computer. The heel bone mineral density before and after treatment was measured by calcaneal quantitative ultrasound (GE-1000 Express). Results: The study included 23 residents but 3 patients developed fractures and 1 withdrew from the study. Nineteen elder residents (average age 86.9 years) completed the study with ultrasonic quantitation before and after treatment. The average speed of sound (following SOS) of the treated and non-treated side was 1438.3 and 1437.4 m/s, respectively at baseline. After 3 months, the SOS was increased to 1450.8 and 1450.5 m/s, respectively, and after 8 months it increased to, 1452.8 and 1451.6 m/s. There were no significant changes between the treated and the non-treated side of the heel bone. Discussion: LIPUS had no effect on increasing bone density in the elderly residents when treatment duration was 2 minutes per day. We suggest that therapy for osteoporosis with LIPUS for the elderly should be studied in the future to reduce the number of prescribed oral agents.